2020
DOI: 10.1002/jcla.23366
|View full text |Cite
|
Sign up to set email alerts
|

Increased CCL24 and CXCL7 levels in the cerebrospinal fluid of patients with neurosyphilis

Abstract: Background Monocytes are recruited into the cerebrospinal fluid (CSF) of patients with neurosyphilis, suggesting abnormal chemokine expression. We aimed to investigate the aberrant expression of chemokines in the CSF of these patients. Methods CSF and serum samples were collected from patients with neurosyphilis between July 2017 and June 2019 in the Dermatology Department, Second Affiliated Hospital of Zhejiang University. Differences in the expression of 38 chemokines between patients with and without neuros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…gastric cancer ( Chen et al, 2022 ) and thyroid carcinoma ( Zhang et al, 2021b )), inflammation ( e.g . rheumatoid arthritis ( Guerrero et al, 2021 )), neurosyphilis ( Li et al, 2020 ), COVID-19 ( Yatim et al, 2021 ), and metabolic disease ( e.g . diabetes mellitus ( Moin et al, 2021 ; Zhang et al, 2021a )).…”
Section: Discussionmentioning
confidence: 99%
“…gastric cancer ( Chen et al, 2022 ) and thyroid carcinoma ( Zhang et al, 2021b )), inflammation ( e.g . rheumatoid arthritis ( Guerrero et al, 2021 )), neurosyphilis ( Li et al, 2020 ), COVID-19 ( Yatim et al, 2021 ), and metabolic disease ( e.g . diabetes mellitus ( Moin et al, 2021 ; Zhang et al, 2021a )).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CXCL7 gene expression was upregulated in dendritic cells in response to B. garinii stimulation compared with unstimulated and LPS-stimulated cells [ 81 ], which might be due to platelet contamination however. During a different spirochetal infection, neurosyphilis, elevated CXCL7 concentrations in the cerebrospinal fluid were reported [ 82 ]. Finally, we found that the addition of recombinant CXCL7 increased cytokine production in an in vitro PBMC model of B. burgdorferi stimulation, supporting an active role for CXCL7 in the inflammatory response to B. burgdorferi.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL7 has mostly been found to be expressed in tumor cells to promote their proliferation or migration [ 40 ]. CXCL7 released by vascular endothelial cells has been identified as a chemoattractant for human neural stem cells, with its level rising in the cerebrospinal fluid in bacterial meningitis and neurosyphilis [ 41 ]. To the best of our knowledge, this is the first study to show that CXCL7 has an extremely high expression in PVN of rats, although such expression decreased upon SIH.…”
Section: Discussionmentioning
confidence: 99%